EFFECTS OF APPLYING LIQUID ORGANIC FERTILIZER FROM NONI FRUIT (Morinda citrifolia L.) ON THE BIOMASS OF Lemna sp. IN THE CULTURE MEDIA FOR NILE TILAPIA (Oreochromis niloticus) - Yulisa Rika Sari; Saberina Hasibuan; Rodhi Firmansyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
Lemna sp. is an aquatic plant with high nutritional content, especially protein, and can grow rapidly in favorable environmental conditions. In addition to being a food source, Lemna sp. acts as a phytoremediator by absorbing ammonia, nitrate, and phosphate compounds derived from feed residues and fish metabolism. This study aims to investigate the use of Liquid Organic Fertilizer (LOF) derived from noni fruit to support the growth of Lemna sp. in tilapia fish culture media. The study was conducted from September to October 2025 at the Aquaculture Environmental Quality Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Riau. This study used an experimental method. The experimental design used a Completely Randomized Design (CRD) consisting of 5 treatment levels and 3 replications so that there were a total of 15 treatment units, namely P0: Without giving noni fruit POC, P1: Giving noni fruit LOF 1.75 mL/L, P2: Giving noni fruit LOF 2 ml/L, P3: Giving noni fruit LOF 2.25 ml/L, P4: Giving noni fruit LOF 2.5 ml/L. The results of the study showed that the administration of noni fruit LOF at a dose of 2.5 ml/L was the best treatment for the growth of absolute weight in Lemna sp, with an average absolute weight of 145.66 ± 4.81 g and a specific growth rate of 4.70 ± 0.08% / day. Treatment with this dose was able to support the growth of tilapia for 30 days without commercial feed and only using Lemna sp as a single feed by producing an absolute weight of tilapia of 1.71 ± 0.10 g, an absolute length of 2.8 ± 0.11 cm, a specific growth rate of 3.22 ± 0.07 % / day, and a survival rate of 96%. In addition, the presence of Lemna sp in the maintenance medium acts as a phytoremediation agent, helping maintain stable water quality. Water quality parameters during the study remained within a reasonable range, with temperatures ranging from 26.4–30.1℃, pH 6.0–7.9, DO 4.1–7.2 mg/L, nitrate 0.06–19.05 mg/L, phosphate 0.13–4.16 mg/L, and ammonia 0.01–0.02 mg/L, supporting tilapia survival and growth.